2017
DOI: 10.1093/femsle/fnx015
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic exposure and bacterial resistance in human and veterinary medicine: a problem-based learning topic for master's students

Abstract: This report describes a problem-based learning activity concerning antibiotic exposure and bacterial resistance in human and veterinary medicine. In addition, learning outcomes and satisfaction of students were recorded by the supervisors of the activity. The students all participated actively in the group work and considered that the small size of the group facilitated interpersonal communication. They believed that working in an interdisciplinary group helped them learn better than if they were following spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, when you graduate from school and look for work in the industrial world, you are ready and mature in your work (Peters, 2015). Moreover, veterinary students in Myanmar, France, Senegal, Vietnam, and Cameroon solve problems through PBL (Eveillard et al, 2017). Another case is in Japan, where PBL solves problems in the operating room (Komasawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when you graduate from school and look for work in the industrial world, you are ready and mature in your work (Peters, 2015). Moreover, veterinary students in Myanmar, France, Senegal, Vietnam, and Cameroon solve problems through PBL (Eveillard et al, 2017). Another case is in Japan, where PBL solves problems in the operating room (Komasawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the research of Cresswell and Loughlin (2017), they concluded that a case-based scenario with an interdisciplinary guidedinquiry experience in chemistry and biology courses enabled the undergraduate forensic science students to have positive opinions especially about group work and the students expressed that the developed and implemented scenario was more interesting. In their research, Eveillard et al (2017) concluded that Master's students expressed positive opinions about that they participated actively in the group work and group work facilitated interpersonal communication in PBL approach concerning antibiotic exposure and bacterial resistance in human and veterinary medicine. In their research of Tarkın and Uzuntiryaki-Kondakcı (2017), they concluded that the secondary school students had positive opinions about that chemistry lessons were more interesting and enjoyable via case-based instruction concerning the topic of electrochemistry.…”
Section: Introductionmentioning
confidence: 99%